Novel Method For Measurement Of Aortic Pulse Wave Velocity By Photoelectric Pulse Transducer Coupled With ECG: A Pilot Study - SATISH.G.PATIL; G.B.DHANAKSHIRUR; MANJUNATHA R AITHALA; SANTOSH PALEKAR (International Journal of Pharma and Bio Sciences, 2012)
Arterial stiffness is considered an increasingly important biomarker in the evaluation of cardiovascular risk. The gold standard for assessment of arterial stiffness is measurement of aortic pulse wave velocity (PWV). The aim of the present study is to establish a new method for measurement of aortic PWV by using Photoelectric technique coupled with ECG. We studied 36 healthy male subjects between the age of 18 to 60 years. To measure aortic PWV, pulse wave were recorded at the site of right Carotid and Femoral artery by Photoelectric pulse transducer for 10 sec to obtain 6-12 beats with simultaneous recording of ECG. The average time in seconds elapsed between the peak of the R-wave of ECG and the foot of the pulse waves were calculated. Distance in meters from sternal notch to carotid pulse site and distance from sternal notch to groin were measured. Difference in distance (ΔD) divided by time difference (Δt) were given the velocity. The aortic PWV ranges between 4.7 to 10.7 m/s. The values obtained are in accordance with the established methods. Reproducibility of our method was good with very low variability in both interobserver and intraobserver analysis. We conclude that measurement of aortic PWV by photoelectric technique gated with ECG can prove as a simple, reliable and cost effective method.